Topographies of 'care pathways' and 'healthscapes': reconsidering the multiple journeys of people with a brain tumour. Issue 3 (12th December 2017) - Llewellyn, Henry; Higgs, Paul; Sampson, Elizabeth L; Jones, Louise; Thorne, Lewis
Abstract: People diagnosed with brain tumours enter new and unfamiliar worlds in which they must make complex and previously unimaginable decisions about care, treatment and how to live their lives. While decisions are increasingly based around care pathways, these are embedded in values that often fail to accord with those of patients. In this article, we examine the cases of people with a brain tumour and how they, their families and healthcare professionals navigate and intervene in the course of life‐threatening disease. We use ethnographic data (2014–16) and modified social theory to highlight: (1) patients' interpretations of disease and care and how they might differ from dominant biomedical logics; (2) complexity and contingency in care decisions; (3) rapid and unanticipated change owing to disease and bodily change; and (4) how people find ways through a world that is continually in motion and which comes into being through the combined action of human and non‐human agencies. Our modified 'healthscapes' approach provides an analytic that emphasises the constant precariousness of life with a brain tumour. It helps to explain the times when patients' feel bumped off the pathway and moments when they themselves step away to make new spaces for choice.